Develop advanced ceramic electrochemical cells for future sustainable energy solutions - Liu, Fan (Kansas State University, 2024)
Ceramic electrochemical cells can operate in both fuel cell and steam electrolysis modes for efficient power generation, green hydrogen production and CO₂ conversion. In fuel cell mode, they can efficiently convert the chemical energy contained within hydrogen, hydrocarbons, and ammonia to electricity. In electrolysis mode, they can operate with applied power from a renewable source (e.g., solar) to produce hydrogen or synthesize chemicals. Although some intriguing demonstrations of intermediate-temperature (500-600 °C) protonic ceramic electrochemical cells (IT-PCECs) have been made in the last decade, the operating temperature of PCECs is still too high to revolutionize ceramic electrochemical cell technology. Bringing the operating temperature down to 275-450 °C can entirely transform the architecture and operation of ceramic electrochemical cell systems. For example, inexpensive stainless-steel interconnects, polymeric sealants, and ready-made balance of plants (BOPs) can be used, while the thermal cycling stability, system reliability, and applicability in portable power, transportation markets, and distributed chemical manufacturing industries can be enhanced. Working in the fuel cells mode, PCECs, which employ proton-conducting oxide as the electrolyte could intensify power generation and chemical manufacturing, such as drying reforming of methane (DRM). DRM occurs at the PCEC anode, where CO₂ reacts with CH₄ to produce H₂ and CO. Air is fed to the PCEC cathode; thus, PCECs function as fuel cells to generate electricity. One unique feature of PCECs is that water is produced at the cathode; therefore, the chemicals produced at the anode are not diluted. As the counterpart of PCECs, solid oxide fuel cells (SOFCs) stand as another highly promising electrochemical energy conversion technology, effectively converting chemical energy into electricity. In contrast to polymer electrolyte membrane fuel cells, which rely on high-purity hydrogen, the exceptional fuel flexibility of ceramic electrochemical cells vastly expands their potential applications. Among the various fuel-flexible SOFCs, direct-methane SOFCs (CH₄-SOFCs) hold intrigue due to the cost-effectiveness of methane compared to other commercially available fuels. Furthermore, liquified natural gas (LNG) has a relatively high volumetric energy density, which is a crucial factor for vehicular applications. However, the deployment of CH₄-SOFCs in transportation necessitates operation at relatively low temperatures (e.g., < 650 °C) to mitigate thermal cycling risks. Additionally, the fuel mixture supplied to CH₄-SOFCs, typically a blend of methane and steam, should maintain a low steam-to-carbon (S:C) ratio. Moreover, excessive steam can dilute the fuel, resulting in suboptimal fuel cell performance. Therefore, the successful integration of CH₄-SOFCs for vehicular applications hinges on their operation under a low S:C ratio and below 650 °C. Working in electrolysis mode, converting CO₂ into valuable chemicals in PCECs has attracted growing attention, which is attributed to their unique advantages over low-temperature (<100 °C) polymer electrolyte membrane electrochemical cells and high-temperature (>700 °C) oxygen-ion solid oxide electrolysis cells. The primary advantage of PCECs is their intermediate operating temperatures (300-600 °C), which thermodynamically and kinetically favor the CO₂ reduction chemistry at the negative electrode, allowing the production of chemicals beyond CO while achieving high energy efficiencies. However, previous PCECs that are equipped with Ni cermet-based negative electrodes, such as BaZr[subscript 0.8-x]Ce[subscript x]Y[subscript 0.2]O[subscript 3-𝛿]-Ni or BaZr[subscript 0.8-x]Ce[subscript x]Y[subscript 0.1]Yb[subscript 0.1]O[subscript 3-𝛿]-Ni, cannot reduce CO₂ to either CH₄ or CO with a selectivity of >99 %, leading to the production of a CO and CH₄ mixture. Therefore, tailoring the negative electrode, which enables selective production of a specific chemical, is essential for the implementation of CO₂-PCECs. In order to address above challenges, this PhD thesis focusing on developing highly efficient and durable PCECs/SOFCs for future sustainable energy solutions, both on fuel cell mode and electrolysis mode. Firstly, in order to lowering the operation temperature of PCECs, we present two main approaches to reducing electrolyte ohmic resistance, electrolyte-positive electrode contact resistance, and electrode polarization resistance, which enables PCECs operation at <450 °C, setting several new records for PCECs. First, by using the ultrasonic spray coating system to coat the electrolyte layer on a negative electrode substrate with low Ba-deficiency, a bamboo-structured, ultrathin, and chemically homogeneous electrolyte can be fabricated. The ohmic area specific resistance (ASR₀) is reduced to 0.19 Ω cm² at 450 °C, which is lower and comparable to the PCEC electrolyte fabricated via costly and unscalable pulsed laser deposition (PLD) techniques. Second, a newly self-assembled composite positive electrode, Ba[subscript 0.62]Sr[subscript 0.38]CoO[subscript 3-δ]-Pr[subscript 1.44]Ba[subscript 0.11]Sr[subscript 0.45]Co[subscript 1.32]Fe[subscript 0.68]O[subscript 6-δ] (SA-BSC+PBSCF), enhances the interfacial bonding between the positive electrode and electrolyte, further reducing ASR₀, while improving both bulk oxygen-ion diffusion coefficient and surface oxygen exchange coefficient at <450 °C, significantly decreasing the ASR[subscript P] and allowing an extraordinarily low ASR[subscript P] of 0.38 Ω cm² to be achieved at 450 °C (versus the 0.76 Ω cm² ASR[subscript P] of the state-of-the-art positive electrode). The newly developed LT-PCECs attain outstanding power densities in fuel cell mode (as high as 0.77 W cm⁻² in H₂ at 450 °C), and exceptional current densities in water electrolysis mode (over -1.28 A cm⁻² at 1.4 V and 450 °C). First, the LT-PCECs attain exceptional fuel cell performance at even 275 °C, with a practical power density of 0.1 W cm⁻² on H₂. At 400 °C, the PCECs that operate in electrolysis mode achieve a high energy efficiency of >85% at a current density of 0.4 A cm⁻². Exceptional durability has been also demonstrated in both fuel cell and electrolysis modes at <450 °C. We tested the PCECs at 400 °C and a current density of 0.6 A cm⁻² for >250 h, achieving negligible degradation in the applied voltage, Faradaic efficiency, and energy efficiency. This thesis also demonstrates process-intensified DRM-PCECs for concurrent power generation, chemical production, and greenhouse gas mitigation, with unprecedented performance at intermediate temperatures (<650 °C). To achieve unprecedented performance, Sm[subscript 0.2]Ce[subscript 0.7]Ni[subscript 0.1]Ru[subscript 0.05]O[subscript 2-δ] (SDC-Ni-Ru) was pioneered to improve DRM activity, which leads to higher fuel cell performance and higher syngas production rates than with Sm[subscript 0.2]Ce[subscript 0.7]Ni[subscript 0.15]O[subscript 2-δ] (SDC-Ni) and Sm[subscript 0.2]Ce[subscript 0.7]Ru[subscript 0.15]O[subscript 2-δ] (SDC-Ru) and yields enhanced coking tolerance. The synergy between Ni and Ru simultaneously facilitates CO₂ activation and CH₄ activation. Moreover, CO₂ can be readily activated over SDC-Ni-Ru, which subsequently accelerates the oxidation of -CH* species formed on the Ni surface, inhibiting the decomposition of -CH* to carbon and hydrogen and consequently enhancing coking tolerance. By coating SDC-Ni-Ru on the PCEC anode as the internal DRM catalytic layer, the operating temperature of DRM-PCECs was lowered to 550-650 °C, achieving a groundbreaking power density of ~0.94 W cm⁻² at 650 °C and 0.30 W cm⁻² at temperatures as low as 550 °C. To underscore the practical implications of SDC-Ni-Ru catalyst, we successfully applied it as CH₄-SOFC internal anode reforming layer. This innovative approach also resulted in remarkable improvements in both peak power densities (PPDs) and operational stability (>2000 hours) Finally, we have validated the potential of applying PCECs for CO₂ electrochemical conversion. We disclose results on an oxide-supported in-situ exsolved Ni-Fe alloyed nanoparticle electrocatalyst, SFM-Ni0.175, which is first employed as the negative electrode of PCECs. The PCECs equipped with this new negative electrode selectively favor the CO₂-to-CO conversion. A selectivity of ~100% toward CO has been demonstrated over a wide range of operating temperatures (400-600 °C) and applied potential/current density. The negative electrode demonstrated in this work fully suppresses the CH₄ production. Furthermore, SFM-Ni0.175 dramatically reduces the overpotential attributed to the negative electrode while increasing the CO production rate. In situ diffuse reflectance infrared spectroscopy (DRIFTS) was performed to probe the CO₂ reduction mechanisms over both SFM-Ni0.175 and the traditional negative electrode (BCZYYb7111+Ni), which indicates SFM-Ni0.175 inhibits the formation of formate species, leading to selective production of CO. Overall, this PhD thesis presents an extensive and thorough investigation into the advanced design and development of ceramic electrochemical cells, addressing their multifaceted applications across various applications such as electricity generation, hydrogen production, CO₂ reduction, and chemical manufacturing. Through systematic research and experimentation, this study endeavors to enhance the performance, efficiency, and versatility of ceramic electrochemical cells to meet the growing demands of sustainable energy solutions. Through a combination of theoretical analysis, experimental validation, and technological advancements, the research presented herein seeks to bridge the gap between fundamental understanding and practical application, paving the way towards a more sustainable and environmentally conscious future.
Keywords: Proton conductor; Fuel cells; Electrolysis; CO2 conversion; H2 production; Energy conversion and storage